PENGARUH DANA PIHAK KETIGA DAN NON PERFORMING FINANCING TERHADAP LIKUIDITAS BANK BNI SYARIAH PERIODE 2011-2020: PENGARUH DANA PIHAK KETIGA DAN NON PERFORMING FINANCING TERHADAP LIKUIDITAS BANK BNI SYARIAH PERIODE 2011-2020 - Bachtiar, Eko; Farindah, Memi (Jurnal Keuangan dan Perbankan Syariah, 2020)
ABSTRACT The purpose of this study was to find out the Effect of Third Party Funds on Liquidity, the Effect of Non Performing Financing on Liquidity and the effect of Third Party Funds and Non Performing Financing simultaneously on BNI Syariah Bank Liquidity in the 2011-2020 period. This research is a quantitative research. The data source used is secondary data with the Quarterly financial reports of the BNI Syariah bank from 2011-2020 obtained from the official website data of the Financial Services Authority (OJK). The data collection technique used is Library Research. The method used in this study is multiple linear regression analysis by conducting classic assumption tests, namely the normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. After that, the F test, T test and R-square coefficient of determination test were carried out with a significance of 5% or 0.05. Based on the analysis conducted, it can be concluded that DPK has a negative and significant effect on liquidity. NPF has a positive and significant effect on Liquidity. The results of the F test count = 6.544 and a significance of 0.004, meaning that a significance value of 0.004 <0.05 means that the significance value of the F test is less than ? = 5%, stating that TPF and NPF together affect liquidity.